Characterization of the major fragance gene from an aromatic japonica rice and analysis of its diversity in Asian cultivated rice - Bourgis, Fabienne; Guyot, R.; Gherbi, H; Tailliez, E; Amabile, I; Salse, J; Lorieux, Mathias; Delseny, M; Ghesquière, Alain (Springer, 2008)
In Asian cultivated rice (Oryza sativa L.), aroma is one of the most valuable traits in grain quality and 2-ACP is the main volatile compound contributing to the characteristic popcorn-like odour of aromatic rices. Although the major locus for grain fragrance (frg gene) has been described recently in Basmati rice, this gene has not been characterised in true japonica varieties and molecular information available on the genetic diversity and evolutionary origin of this gene among the different varieties is still limited. Here we report on characterisation of the frg gene in the Azucena variety, one of the few aromatic japonica cultivars. We used a RIL population from a cross between Azucena and IR64, a non-aromatic indica, the reference genomic sequence of Nipponbare (japonica) and 93–11 (indica) as well as an Azucena BAC library, to identify the major fragance gene in Azucena. We thus identified a betaine aldehyde dehydrogenase gene, badh2, as the candidate locus responsible for aroma, which presented exactly the same mutation as that identified in Basmati and Jasmine-like rices. Comparative genomic analyses showed very high sequence conservation between Azucena and Nipponbare BADH2, and a MITE was identified in the promotor region of the BADH2 allele in 93–11. The badh2 mutation and MITE were surveyed in a representative rice collection, including traditional aromatic and non-aromatic rice varieties, and strongly suggested a monophylogenetic origin of this badh2 mutation in Asian cultivated rices. Altogether these new data are discussed here in the light of current hypotheses on the origin of rice genetic diversity.